Aedes aegypti entomological indices in an endemic area for dengue in Sao Paulo State, Brazil - Favaro, Eliane A; Dibo, Margareth R; Pereira, Mariza; Chierotti, Ana P; Rodrigues-Junior, Antonio L; Chiaravalloti-Neto, Francisco (Revista de Saúde Pública, 2013)
OBJECTIVE: To evaluate the most productive types of properties and containers for Aedes aegypti and the spatial distribution of entomological indices. METHODS: Between December 2006 and February 2007, the vector's immature forms were collected to obtain entomological indices in 9,875 properties in the Jaguare neighborhood of Sao Jose do Rio Preto, SP, Southeastern Brazil. In March and April 2007, a questionnaire about the conditions and characteristics of properties was administered. Logistic regression was used to identify variables associated with the presence of pupae at the properties. Indices calculated per block were combined with a geo-referenced map, and thematic maps of these indices were obtained using statistical interpolation. RESULTS: The properties inspected had the following Ae. aegypti indices: Breteau Index = 18.9, 3.7 larvae and 0.42 pupae per property, 5.2 containers harboring Ae. aegypti per hectare, 100.0 larvae and 11.6 pupae per hectare, and 1.3 larvae and 0.15 pupae per inhabitant. The presence of yards, gardens and animals was associated with the presence of pupae. CONCLUSIONS: Specific types of properties and containers that simultaneously had low frequencies among those positive for the vector and high participation in the productivity of larvae and pupae were not identified. The use of indices including larval and pupal counts does not provide further information beyond that obtained from the traditional Stegomyia indices in locations with characteristics similar to those of São José do Rio Preto. The indices calculated per area were found to be more accurate for the spatial assessment of infestation. The Ae. aegypti infestation levels exhibited extensive spatial variation, indicating that the assessment of infestation in micro areas is needed.